CYTOTOXICITY OF MUSSAENDA PHILIPPICA AGAINSTARTEMIA SALINA AND CANCER CELL LINES - RENILDA SOPHY A.J.,; ALBIN T. FLEMING, (International Journal of Pharma and Bio Sciences, 2016)
Many herbs are evaluated for their different bioactivity, but there had been limited screening of the bioactive compounds from the ornamental plants. The ornamental plant, Mussaenda philippica of the family Rubiaceae, is known for its colourful sepals. The toxicity of the leaf extracts of M. philippica was evaluated by a preliminary assay using Artemia salina and anticancer activity was assessed using in vitro studies against two cancer cell lines, NCI-H460 and HCT116. The LD50 value of the ethanol extracts showed a high value of 856.91µg/mL against brine shrimp and the chloroform extract showed a low value of 520.40µg /mL. The chloroform, ethyl acetate and ethanol extracts showed a significant growth inhibition of both the cancer cell lines. Both the cytotoxicity studies suggest the presence of bioactive compounds in the extracts.